1993
DOI: 10.1097/00001888-199302000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of examinee gender, standardized-patient gender, and their interaction on standardized patientsʼ ratings of examineesʼ interpersonal and communication skills

Abstract: Except for the women examinee's higher performance in personal manner, the men and women examinees generally performed equally well with respect to interpersonal and communication skills, and they performed equally well regardless of the gender of the SP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 0 publications
3
24
0
Order By: Relevance
“…However, the authors also found that the interaction was not significant when comparing mean scores on the written question exercise administered after SP encounters. For ratings of interpersonal and communication skills, male and female students performed equally well, regardless of the gender of the SP (Colliver et al, 1993). Rutala et al (1991) found a significant interaction between SP gender and student scores with female students receiving significantly higher scores for encounters with female SPs.…”
Section: Introductionmentioning
confidence: 98%
“…However, the authors also found that the interaction was not significant when comparing mean scores on the written question exercise administered after SP encounters. For ratings of interpersonal and communication skills, male and female students performed equally well, regardless of the gender of the SP (Colliver et al, 1993). Rutala et al (1991) found a significant interaction between SP gender and student scores with female students receiving significantly higher scores for encounters with female SPs.…”
Section: Introductionmentioning
confidence: 98%
“…The gender of the examiner as a possible factor of bias was evaluated in other studies. In some studies, female examiners tend to score higher [12, 13], whereas many other studies could not confirm a gender-related effect [1416]. In contrast, other studies found that male examiners score female students higher [17].…”
Section: Introductionmentioning
confidence: 99%
“…health professionals) will closely resemble their actual behavior in a clinical situation (Dresselhaus, Peabody, Luck, & Bertenthal, 2004;Jones, Gerrity, & Earp, 1990). Vignettes are often used as an effective and cheaper alternative to standardized patients (Colliver & Swartz, 1997;Colliver, Vu, Marcy, Travis, & Robbs, 1993) or direct observation (Glassman, Rolph, Petersen, Bradley, & Kravitz, 1996;Peabody, Luck, Glassman, Dresselhaus, & Lee, 2000). For many years, clinical vignettes have been seen as a useful tool for continuing professional development (Mettes et al, 2010).…”
Section: Introductionmentioning
confidence: 99%